Effects of functional suspension training on l-sit cross in still rings for Egyptian elite male artistic gymnasts - Osama, E.-E. E.-A. (Science, Movement & Health, 2018)
Effects of functional suspension training on l-sit cross in still rings for egyptian elite male artistic gymnasts OSAMA Ezz-Elregal El-Awady1 Abstract Aim. The L-sit is an isometric movement, The L-sit performance depended on variety of muscles throughout your body but targets your abs, arms -- particularly your triceps -- and hip flexors. The training with the TRX can stimulate the motor and capacity aspects such as speed, resistance, flexibility and coordination, as well as the activation of each energy system. The purpose of this study was to investigate the effect of functional suspension training on L-sit cross in still rings for Egyptian elite male artistic gymnasts. Methods. The sample comprised random from elite gymnasts in El-Maady club. (20) gymnasts, the subjects divided into two groups. The experimental group (n= 10) participated in functional suspension training program four- times weekly. To eight weeks. The control group (n= 10) participated in the traditional program only. Results. Significant Difference between the experimental group and control group in Leg strength, Back strength, Core strength and performance level of L-sit cross for the experimental group. Conclusions. Finally, the findings indicated that the functional suspension training for eight weeks could an improvement in Leg strength, Back strength, Core strength and performance level of L-sit cross for the experimental group. These results have to be taken into account by Trainers in order to better understand and implicated of these concepts in training sessions and lessons.